Constitutive Mutants in a Regulatory Gene Exerting Positive Control of Quinic Acid Catabolism in Neurospora crassa - Valone, James A. (1971)
In Neurospora crassa, evidence has recently been obtained for a cluster of four closely-linked genes controlling the inducible enzymes catalyzing the first three reactions in the catabolism of quinic acid. Three of these genes appear to be the structural genes for the three enzymes. The fourth gene, designated qa-1, has been interpreted as having a regulatory function, since qa-1 mutants are pleiotropic types, are noninducible for the three enzymes, and form heterocaryons which complement mutants in the structural genes. The present studies were undertaken to elucidate further the nature of the regulatory role of the qa-1 locus. A number of constitutive (qa-1(C)) mutants have been obtained from certain qa-1 mutants as revertants selected for their ability to grow on quinic acid as a sole source of carbon. These qa-1(C) mutants produce high levels of all three enzymes in the absence of an inducer, map within (or very close to) the qa-1 locus, and produce a catabolic dehydroquinase (EC 4.2.1.10) which is indistinguishable, on the basis of thermolability tests, from that of wild type. In addition, when grown in the absence of an inducer, heterocaryons between wild-type (qa-1(+)) and different qa-1(C) mutants exhibit markedly different levels of constitutivity (from 5 to 50% of the particular parental qa-1(C) mutant) for catabolic dehydroquinase, one of the enzymes under qa-1 control. These overall results are interpreted as supporting the hypothesis that the qa-1(+) gene product (presumably a multimeric protein) plays only a positive regulatory role in initiating synthesis of the three quinate catabolic enzymes.